Cerebral Small Vessel Disease and Functional Outcome Prediction After Intracerebral Hemorrhage. (13th April 2021) - Hostettler, Isabel C.; Schwarz, Ghil; Ambler, Gareth; Wilson, Duncan; Banerjee, Gargi; Seiffge, David J.; Shakeshaft, Clare; Lunawat, Surabhika; Cohen, Hannah; Yousry, Tarek A.; Al-Shahi Salman, Rustam; Lip, Gregory Y.H.; et al.
Abstract : Objective: To determine whether CT-based cerebral small vessel disease (SVD) biomarkers are associated with 6-month functional outcome after intracerebral hemorrhage (ICH) and whether these biomarkers improve the performance of the preexisting ICH prediction score. Methods: We included 864 patients with acute ICH from a multicenter, hospital-based prospective cohort study. We evaluated CT-based SVD biomarkers (white matter hypodensities [WMH], lacunes, brain atrophy, and a composite SVD burden score) and their associations with poor 6-month functional outcome (modified Rankin Scale score >2). The area under the receiver operating characteristic curve (AUROC) and Hosmer-Lemeshow test were used to assess discrimination and calibration of the ICH score with and without SVD biomarkers. Results: In multivariable models (adjusted for ICH score components), WMH presence (odds ratio [OR] 1.52, 95% confidence interval [CI] 1.12–2.06), cortical atrophy presence (OR 1.80, 95% CI 1.19–2.73), deep atrophy presence (OR 1.66, 95% CI 1.17–2.34), and severe atrophy (either deep or cortical) (OR 1.94, 95% CI 1.36–2.74) were independently associated with poor functional outcome. For the revised ICH score, the AUROC was 0.71 (95% CI 0.68–0.74). Adding SVD markers did not significantly improve ICH score discrimination; for the best model (adding severe atrophy), the AUROC was 0.73 (95% CI 0.69–0.76). These results were confirmed when lobar and nonlobar ICH were considered separately. Conclusions: The ICH score has acceptable discrimination for predicting 6-month functional outcome after ICH. CT biomarkers of SVD are associated with functional outcome, but adding them does not significantly improve ICH score discrimination. Trial Registration Information: ClinicalTrials.gov Identifier: NCT02513316.